The evolution of the idea of religious determinism in the Middle Ages - Shatalovych, Inna (Actual Problems of Mind, 2017)
The article is devoted to revealing the forms of religious determinism in the Middle Ages. The evolution of the ideas of determinism is considered on the basis of the works of Augustine, Boethius, Thomas Aquinas.